Genetic Polymorphisms Complicate COVID-19 Therapy: Pivotal Role of HO-1 in Cytokine Storm - Eddie W. Fakhouri; Stephen J. Peterson; Janish Kothari; Ragin Alex; Joseph I. Shapiro; Nader G. Abraham (MDPI AG, 2020)
Coronaviruses are very large RNA viruses that originate in animal reservoirs and include severe acute respiratory distress syndrome (SARS) and Middle East respiratory syndrome (MERS) and other inconsequential coronaviruses from human reservoirs like the common cold. SARS-CoV-2, the virus that causes COVID-19 and is believed to originate from bat, quickly spread into a global pandemic. This RNA virus has a special affinity for porphyrins. It invades the cell at the angiotensin converting enzyme-2 (ACE-2) receptor and binds to hemoproteins, resulting in a severe systemic inflammatory response, particularly in high ACE-2 organs like the lungs, heart, and kidney, resulting in systemic disease. The inflammatory response manifested by increased cytokine levels and reactive oxygen species results in inhibition of heme oxygenase (HO-1), with a subsequent loss of cytoprotection. This has been seen in other viral illness like human immunodeficiency virus (HIV), Ebola, and SARS/MERS. There are a number of medications that have been tried with some showing early clinical promise. This illness disproportionately affects patients with obesity, a chronic inflammatory disease with a baseline excess of cytokines. The majority of the medications used in the treatment of COVID-19 are metabolized by cytochrome P450 (CYP) enzymes, primarily CYP2D6. This is further complicated by genetic polymorphisms of CYP2D6, HO-1, ACE, and ACE-2. There is a potential role for HO-1 upregulation to treat/prevent cytokine storm. Current therapy must focus on antivirals and heme oxygenase upregulation. Vaccine development will be the only magic bullet.